2021
DOI: 10.1093/imrn/rnaa324
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Proof of Conjectures on Cycle Lengths in Graphs

Abstract: In this paper, we prove a tight minimum degree condition in general graphs for the existence of paths between two given endpoints whose lengths form a long arithmetic progression with common difference one or two. This allows us to obtain a number of exact and optimal results on cycle lengths in graphs of given minimum degree, connectivity or chromatic number. More precisely, we prove the following statements by a unified approach: 1. Every graph $G$ with minimum degree at least $k+1$ contains c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Confirming a conjecture of Erdős [5], Kostochka, Sudakov and Verstraëte [12] showed that if such G does not contain a triangle, then it contains at least Ω(k 2 log k) cycles of consecutive lengths. Recently, the authors and Liu [9] proved a conjecture of Sudakov and Verstraëte [20] that such G contains k − 1 cycles of consecutive lengths. We remark that Theorem 1.1 and these results of [9,16] are all tight for G being the clique K k+1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirming a conjecture of Erdős [5], Kostochka, Sudakov and Verstraëte [12] showed that if such G does not contain a triangle, then it contains at least Ω(k 2 log k) cycles of consecutive lengths. Recently, the authors and Liu [9] proved a conjecture of Sudakov and Verstraëte [20] that such G contains k − 1 cycles of consecutive lengths. We remark that Theorem 1.1 and these results of [9,16] are all tight for G being the clique K k+1 .…”
Section: Introductionmentioning
confidence: 99%
“…The proof for graphs without a triangle is motivated by [12] and utilizes extremal arguments, where we use a new lemma on A-B paths (see Lemma 3.2). On the other hand, the proof for graphs containing a triangle follows the line of [9] and relies on the structural analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For illustrative purposes let us mention that, confirming a conjecture of Thomassen [12], Gao et al proved [7] that requiring minimum degree δ(G)q+1 guarantees cycles of all even lengths modulo q, including of course cycles of length divisible by q; requiring δ(G)q is necessary to guarantee a cycle of length divisible by q, at least for odd q, as shown by the complete bipartite graph Kq1,n for nq1. In contrast, our result allows to argue about existence of cycles of length divisible by q in much sparser graphs.…”
Section: Introductionmentioning
confidence: 62%
“…There have been numerous powerful methods for embedding paths and cycles developed in the past three decades, such as Robertson and Seymour's work on graph linkage [25] (see also [2,26]), Bondy and Simonovits's use of Breadth First Search [3] (see also [23]), Krivelevich and Sudakov's use of Depth First Search [17] and the use of expanders in a long line of work by Krivelevich (see e.g. his survey [16] and more recently [7]), see also a recent method developed by Gao, Huo, Liu and Ma [9]. Despite these developments and the simple nature of pillars, the innocent looking conjecture of Thomassen has seen no progress in the past thirty years.…”
Section: Resultsmentioning
confidence: 99%